Prognostic predictors for mortality of patients with COVID-19 in an intensive care unit - Hulya Abali; Hatice Kutbay Ozcelik; Esra Akkutuk Ongel; Nazan Beyhan; Fatma Tokgoz Akyil; Seda Tural Onur; Sedat Altin (Journal of Infection in Developing Countries)
Introduction: Fatality due to COVID-19 continues to be a challenge. Timely identification of critical COVID-19 patients is crucial for their close clinical follow-up and treatment. We aimed to identify the mortality predictors of critical COVID-19 patients.